Kontroversi Hacker Bjorka: Analisis Isi Kuantitatif Strategi Pemulihan Citra - Anjani Bharata Ajie; Dian Purworini (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2023)
Cyber Crime in Indonesia in 2022 had a significant increase. One of the cybercrimes was the Bjorka Hacker case. The background of this research is a cybercrime incident committed by Hacker Bjorka against the information security system of the Indonesian government. Hacker Bjorka claimed to have personal data and information of individuals as well as several national organizations. It creates a panic situation among the public. The alleged leak of information makes the Ministry of Communication and Information Technology in the spotlight to be responsible for responding to that crisis situation. Finally, the response of Kominfo becomes very important in this controversy. In order to describe the Kominfo strategy, this research uses quantitative descriptive methods. The population is the statements from Kominfo in response to the Bjorka controversy, that are published in the online media kompas.com in September 2022. The sample is taken by using a purposive sampling method. The results showed that the statements made by Kominfo published by kompas.com were proven to use several strategies for image improvement. The strategies used by Kominfo are denial, corrective action, defeasibility, and minimization. The strategy that is not used is mortification or apologizing.